2020
DOI: 10.1002/ejsp.2706
|View full text |Cite
|
Sign up to set email alerts
|

A social cure in the community: A mixed‐method exploration of the role of social identity in the experiences and well‐being of community volunteers

Abstract: Resilient, cohesive communities are important contributors to the health and well-being of their residents (Ehsan, Klaas, Bastianen, & Spini, 2019). Advances in social psychology suggest a multitude of physical and mental health outcomes derive from meaningful belonging in social groups within a range of contexts (Haslam,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 81 publications
19
85
0
1
Order By: Relevance
“…Alongside direct peer support, clients also discussed how “just having peers there” provided feelings of reassurance. In line with Bowe et al [ 33 ], the presence of peers facilitated enhanced perceptions of social support and safety. Feeling adequately supported and safe are prerequisites for clients to feel confident enough to attend future exercise sessions independently and reach out to other social groups [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…Alongside direct peer support, clients also discussed how “just having peers there” provided feelings of reassurance. In line with Bowe et al [ 33 ], the presence of peers facilitated enhanced perceptions of social support and safety. Feeling adequately supported and safe are prerequisites for clients to feel confident enough to attend future exercise sessions independently and reach out to other social groups [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between well-being and collective identity would explain group membership as a protective factor where members find social support, cohesion, and a sense of communion together with the possibility of deploying collective coping mechanisms and social participation in the face of a disadvantageous social context ( Smith and Silva, 2011 ; Jetten et al, 2017 ; Atari and Han, 2018 ; Bowe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Past research suggests that such strategies are likely to produce a positive effect, as a large amount of time devoted to volunteering activities is a predictor of burnout (63). A recent study has shown that people’s sense of community commitment is often a reason for sustained engagement and that cohesive community relationships are particularly relevant for continuous volunteering over time (30). Yet, and despite the extensive literature on the factors influencing participation in volunteering (64), the predictors of volunteering during the pandemic may be slightly different from others forms of volunteering (45).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of such forms of community volunteering seem to go beyond the context of the pandemic conditions, with previous research suggesting that volunteering may benefit mental health and survival, fostering well-being and life satisfaction (29), as well as sense of belonging (30). In this study, we focus on a broad definition of COVID-19 volunteering, to capture the multiple ways people engaged in community support and mutual aid groups, as well as in community champions programmes.…”
Section: Introductionmentioning
confidence: 99%